A somatosensory test : a pilot study - Lombard, Agnita (Division of Occupational Therapy, 2018)
The most commonly used tests for the evaluation of perceptual motor function of children in South Africa are the Southern California Sensory Integration Tests (Ayres, 1972) and Southern California Postrotary Nystagmus Test (Ayres, 1975). These particular tests were revised, changed and restandardized in 1989. For various reasons the new form, Sensory Integration and Praxis Tests (Ayres, 1989), is not feasible for use in South Africa. It has thus become imperative to develop tests in South Africa that can replace these tests. The South African Institute of Sensory Integration appointed working committees in various sectors of the country to develop a test for the South African population. The candidate decided to develop a somatosensory Test which could be used as part of a South African test of sensory integration. A test was designed and constructed, based on the model used by Ayres in the Southern California Sensory Integration Tests. This test comprises five subtests, i.e. Non-vestibular Proprioception (in the first phase of the study this subtest was named Kinesthesia), Finger Recognition, Form Recognition, Two Point Discrimination and Tactile Stimuli Placement tests. This proposed test was used in the field by seven voluntary field workers. They each recruited a sample of convenience and administered the proposed test to 58 children. A self-administered questionnaire was completed for each test administered completed to evaluate the mechanics of the test. The data obtained from the questionnaires were statistically analysed and from this the candidate could draw conclusions about changes necessary for the test. Suggested changes were implemented. These included shortening the test, changing verbal instructions, adapting some parts of test items, reorganising the score sheet and changing the instruction manual accordingly. A pilot study was conducted to determine validity and reliability of the proposed test. A representative sample (n = 114) was recruited from the Sub A population in the Durbanville and Kraaifontein area of the Northern suburbs of the Cape Town Metropolitan Area. A comparative study was done to validate the proposed test, using the Southern California Sensory Integration Tests as a gold standard. The Two Point Discrimination test was excluded from this validation study as there is no corresponding test of the SCSIT. Results were compared and levels of sensitivity and specificity were established. In general, higher levels of specificity than sensitivity were obtained. The Form Recognition test had the highest sensitivity level (60%) and in the case of the Finger Recognition test statistically significant differences were obtained between means (p = 0.006). Thirty children from the group of 114 were tested by two testers to establish the reliability coefficient. The Form Recognition test had the highest coefficient (0.83).